2019
DOI: 10.1093/femsec/fiz115
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance three ways: healthcare crisis, major concepts and the relevance of biofilms

Abstract: Worldwide, infections are resuming their role as highly effective killing diseases, as current treatments are failing to respond to the growing problem of antimicrobial resistance (AMR). The social and economic burden of AMR seems ever rising, with health- and research-related organizations rushing to collaborate on a worldwide scale to find effective solutions. Resistant bacteria are spreading even in first-world nations, being found not only in healthcare-related settings, but also in food and in the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 214 publications
0
44
0
Order By: Relevance
“…The ability of these pathogens to grow on food matrices often leads to the establishment of microbial communities embedded on a self-produced extracellular matrix, known as biofilms, which confers them protection to antimicrobial agents (Galié, García-Gutiérrez, Miguélez, Villar, & Lombó, 2018). Furthermore, the inappropriate use of antibiotics in both humans and animals (livestock industry) has led to an acceleration of microbial resistance (Jorge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of these pathogens to grow on food matrices often leads to the establishment of microbial communities embedded on a self-produced extracellular matrix, known as biofilms, which confers them protection to antimicrobial agents (Galié, García-Gutiérrez, Miguélez, Villar, & Lombó, 2018). Furthermore, the inappropriate use of antibiotics in both humans and animals (livestock industry) has led to an acceleration of microbial resistance (Jorge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The latter phenomenon is also controlled by the LasI/LasR system by downregulation the expression of PEL, a major biofilm matrix component (Ueda and Wood 2009). QS also influences swarming motility, which has been linked to early stages of biofilm formation (Shrout et al 2006) and is also related to the antibiotic tolerance found in P. aeruginosa biofilms but not in planktonic cells (Ciofu et al 2015;Jorge et al 2019).…”
Section: P Aeruginosa and S Aureus Quorum Sensing Regulationmentioning
confidence: 99%
“…b-lactamase) (Pang et al 2019). P. aeruginosa can also acquire resistance genes from other microorganisms by horizontal gene transfer, while also being able to experience adaptive resistance, as is the case of biofilm formation (Jorge et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these therapies are often unsuccessful, mostly due to biofilms that are microbial communities encased in a self-produced matrix that provide to the resident organisms augmented tolerance to antibiotics (Lopez et al, 2010). Their impressive high level of antimicrobial tolerance results from the combination of several mechanisms, including restricted penetration of antibiotics through the matrix, slow growth of bacteria within biofilms due to nutritional constraints and restricted oxygen penetration, quorum-sensing, expression of biofilm-specific genes, and the presence of persister cells (Mah, 2012;Jorge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%